Solution of volterra integral equations of the second kind with small nonlinearities by a spline-iteration method - Luchka, A. Y.; Mamatov, T. D. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider and justify a spline-iteration method for solving Volterra integral equations of the second kind with small nonlinearities.